Sperm count in Swedish clinical stage I testicular cancer patients following adjuvant treatment. (25th February 2019) - Weibring, K; Nord, C; Ståhl, O; Eberhard, J; Sandberg, K; Johansson, H; Arver, S; Giwercman, A; Cohn-Cedermark, G
Abstract: Background: Little is known regarding sperm production following adjuvant treatment in testicular cancer (TC) clinical stage I (CS I) patients. Patients and methods: A total of 182 TC patients aged 18–50 years were prospectively included during 2001–2006 at any given time within 5 years of orchiectomy. Semen samples were delivered postorchiectomy but before further treatment, 6, 12, 24, 36 and 60 months ( T 0 – T 60 ) after completed therapy. Total sperm number (TSN) and sperm concentration (SC) were used as measurements of testicular function. Four groups according to treatment modality were identified; Radiotherapy; To a total dose of 25.2 Gy to the infradiaphragmal paraaortic and ipsilateral iliac lymph nodes (RT, N = 70), one cycle of adjuvant BEP (bleomycin, etoposide, cisplatin, 5 day regimen) (BEP, N = 62), one cycle of adjuvant carboplatin AUC 7 (Carbo, N = 22), and patients managed by surveillance (SURV, N = 28). Results: In the cross-sectional analysis, a significant but transient drop in mean TSN and mean SC ( T 0 – T 60 ) was seen at T6 after radiotherapy. Apart from a significant increase in mean SC at T12 compared with baseline, no significant differences were observed in the other treatment groups . In 119 patients delivering 3 or more samples, values in TSN and SC were rather stable over time. Azoospermic patients ( N = 11) were observed in most treatment groups except for in the BEP group. During follow-up, one azoospermic patient belonging to the Carbo group became normospermic. Conclusions: No clinically significant long-term effect on TSN or SC associated with adjuvant treatment in TC CSI patients was found. However, as patients may have low sperm counts before orchiectomy as well as after adjuvant treatment, we offer sperm banking before orchiectomy as assisted reproductive measures may be necessary regardless of treatment given.